A comparison of medical therapy and ablation for atrial fibrillation in patients with heart failure. (4th March 2022) - Calvert, Peter; Farinha, José Maria; Gupta, Dhiraj; Kahn, Matthew; Proietti, Riccardo; Lip, Gregory Y. H.
ABSTRACT: Introduction: Atrial fibrillation and heart failure frequently co-exist and the combination is associated with a worse prognosis than either condition alone. A number of pharmacological agents and invasive procedures have been shown to benefit this complex patient group. Objective: In this review, we compare different therapeutic approaches to atrial fibrillation and heart failure, including pharmacotherapy, left atrial catheter ablation and pace-and-ablate. Expert opinion: Left atrial catheter ablation is an efficacious option for restoring sinus rhythm and is most likely to provide benefit to those in whom durable sinus rhythm can be expected, and whose life expectancy is not significantly reduced by other pathologies or advanced age. A pace-and-ablate approach, particularly with physiological pacing, may provide more benefit to those with low chance of maintaining sinus rhythm. Both invasive options generally outperform pharmacotherapy, although it is important to individualize the approach for each patient through shared decision-making.